2020
DOI: 10.31393/bba38-2020-07
|View full text |Cite
|
Sign up to set email alerts
|

Prenosological screening of autonomic regulatory systems tension in secondary school students

Abstract: Adolescence is characterized by increased reactivity to stress factors, among the sources of which the educational environment plays a significant role. The content of education and educational process organization, as well as interpersonal relationships, is the predominant stress factors of the educational environment. In the context of education reform, new pedagogical projects are being introduced, in particular, on the basis of meritocratic education, providing for the intensification of the educational pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Changes in mental capacity were explained by certain features of physiological processes, which coincides with our conclusion on the growth of work performed as a motivational characteristic of mental work, which is associated with physiological and social maturity of ninth graders compared to 6th year schoolchildren. In our previous study on prenosological screening of autonomic regulatory stress in schoolchildren, it was found that the 6th year of study coincides with the sensitive period for autonomic regulatory systems and, accordingly, is characterized by increased sensitivity to environmental factors.At the same time, the higher "price" of adaptation to the meritocratic system of education in 6th grade compared to traditional education is determined not so much by the intensification of the educational process as by interpersonal relationships in educational teams and / or individual psychological characteristics of schoolchildren [31].…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…Changes in mental capacity were explained by certain features of physiological processes, which coincides with our conclusion on the growth of work performed as a motivational characteristic of mental work, which is associated with physiological and social maturity of ninth graders compared to 6th year schoolchildren. In our previous study on prenosological screening of autonomic regulatory stress in schoolchildren, it was found that the 6th year of study coincides with the sensitive period for autonomic regulatory systems and, accordingly, is characterized by increased sensitivity to environmental factors.At the same time, the higher "price" of adaptation to the meritocratic system of education in 6th grade compared to traditional education is determined not so much by the intensification of the educational process as by interpersonal relationships in educational teams and / or individual psychological characteristics of schoolchildren [31].…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…Academic tests are usually perceived by students as challenging stressful situations that elicit a specific cardiac response [ 13 ]. The activity of the heart is strictly regulated by the two branches (sympathetic and parasympathetic) of the autonomic nervous system (ANS) [ 14 ]; on the one hand, sympathetic activation determines increases in heart rate (HR) and stroke volume, and on the other hand, parasympathetic activation of the heart is achieved through the vagus nerve, which acts as a “brake” on HR [ 15 ].…”
Section: Introductionmentioning
confidence: 99%